The utilization of electronic medical records in improving the quality of healthcare facilities: A literature review - Assyifa Ramadhani; Raeesah Wahlullizar; Reynanda Sabrina; Alvamuna Khairani Sudarmaji; Rifa Neisya Azalia Putri; Cahya Arbitera (Indonesian Journal of Health Science, 2026)
Global health digitalization, supported by WHO’s Global Strategy on Digital Health and Indonesia's MoH Regulation No. 24/2022, mandates Electronic Medical Records (EMR) implementation to achieve Universal Health Coverage. However, its execution faces various technical and non-technical barriers. Objective: This systematic literature review aims to analyze and synthesize empirical evidence regarding EMR utilization in improving healthcare service quality and patient safety in Indonesia. Methods: A systematic literature search was conducted through Google Scholar for full-text articles published between 2020 and 2026. Data synthesis was performed using a narrative descriptive approach. Results: EMR implementation significantly enhances healthcare quality by reducing patient waiting times, accelerating clinical decision-making, and mitigating human errors like medication errors. EMR also ensures operational efficiency and heightens patient satisfaction through well-structured documentation. Nevertheless, challenges persist, including unstable networks, limited infrastructure in primary care, low digital literacy, staff resistance, and incomplete data entry. Public health professionals hold a strategic role as change agents and data analysts to optimize EMR governance. Conclusion: EMR serves as a potent digital transformation tool to foster efficient and safe healthcare. Full realization of its benefits heavily relies on systemic readiness, comprising robust technological infrastructure, continuous training to overcome human resource resistance, strong managerial commitment, and national-level system interoperability.